Chaitanya movement in eastern India - Lahiri, Aloka. 1947- (Calcutta : Punthi Pustak, 1993)
On the life and movement of Chaitanya, 1486-1534, Vaishnavite leader of Bengal.
Includes bibliographical references (p. [305]-315) and index.
Keywords: Chaitanya, -- 1486-1534.; Chaitanya (Sect); Vaishnavites -- India